Prediksi Resistensi Udang Vaname (Litopenaus vannamei) terhadap Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV) dari Tambak Intensif dan Semi Intensif Jepara Menggunakan Marka RAPD - Mulyadi, Muhammad; Handayani, Christina Ratna; Kusumaningrum, Hermin Pancasakti; Budiharjo, Anto (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Infectious Hypodermal and Hematopoietic Necrosis Infectious Virus (IHHNV) is the most important DNA virus which can lead to Runt Deformity Syndrome (RDS) in vaname shrimp. The RAPD technique can be used to determine the resistance of a species to a disease. This research aimed to screen and identify RAPD markers which could distinguish the resistance of vaname shrimp to IHHNV reared at intensive and semi-intensive pond. The DNA template was amplified by PCR using 5 primers : OPA 06, OPA 08, OPA 19, OPD-02 and OPZ-15. The results showed that only the primer OPA-19 and OPZ-15 were able to produce 100% polymorphic bands with sizes from 400-1700 bp as well as showing the resistance IHHNV in vaname shrimp. Based on these results, vaname shrimp which reared at the intensive pond were more resistant to IHHNV compared with the semi-intensive pond. Â Key words: RAPD, shrimp vaname, IHHNV, intensive & semi-intensive pond Â